Peningkatan Ketersediaan Darah Sesuai Segmentasi Umur Menggunakan K-Means Clustering - Titania Dwi Andini; Lia Farokhah (Jurnal Manajemen Informatika (JAMIKA), 2022)
Availability of blood at blood banks in Malang city fluctuates unevenly every month and every year. This greatly affects the demand for blood which is very high every day, especially during the current pandemic. To meet the high demand for blood, a program is needed that aims to attract Malang city residents, especially the productive age segment to donate blood so that the availability of blood every month can be met. This study aims to look at blood stock data from BPS (Central Statistics Agency) Malang City every month for three years (2018-2020) which will be clustered / grouped using K-Means method according to the productive age segmentation (17, 18-24, 25-44, 45-59 years) so that it will produce information when there will be an increase in blood donor raising program according to age segmentation by maximizing the month that is the favorite month of the age segmentation and the month that is quiet for donors. This research resulted in cluster groups based on months with analysis on the best number of clusters so that the evaluation resulted in knowledge that the highest month with many donors was October, while the lowest month with few donors was June and December. The government of Malang and related parties can make a program to increase and maximize the blood donor program in that month.